Knowledge exchange with customers using intelligent agents - Homayouni, Seyed Mahdi; Tang, Sai Hong (2008)
Customer gain their own experiences and knowledge through using products or services. This knowledge is recognized as one of the most important competitive resources for the companies in recent years. However the models were introduced in the literature for customer knowledge managment (CKM) focused on the human based interaction with customers to exchange the knowledge. The aim of this paper is to propose the aplicability of agents in knowledge exchange between customers and companies. Autonomy, reactivity and pro activity of agents aid CKM to response the customers as quickly as possible and to customize their services for individuals. The abilities of agents cover the requirements of CKM models. An introductory model is proposed to show the abilities of agents in CKM system. A comparison between agent's abilities and CKM is provided as final goal of this paper.